Cybersecurity all-in-one - Steinberg, Joseph (Cybersecurity expert); Beaver, Kevin; Winkler, Ira; Coombs, Ted (--For dummies., 2023)
"Cybersecurity All-in-One For Dummies covers a lot of ground in the world of keeping computer systems safe from those who want to break in. This book offers a one-stop resource on cybersecurity basics, personal security, business security, cloud security, security testing, and security awareness. Filled with content to help with both personal and business cybersecurity needs, this book shows you how to lock down your computers, devices, and systems--and explains why doing so is more important now than ever. Dig in for info on what kind of risks are out there, how to protect a variety of devices, strategies for testing your security, securing cloud data, and steps for creating an awareness program in an organization."--